2020
DOI: 10.1155/2020/1712604
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Based on a Multiparametric and Multiregional Radiomics Signature Predicts Radiotherapeutic Response in Patients with Glioblastoma

Abstract: Background and Objective. Although radiotherapy has become one of the main treatment methods for cancer, there is no noninvasive method to predict the radiotherapeutic response of individual glioblastoma (GBM) patients before surgery. The purpose of this study is to develop and validate a machine learning-based radiomics signature to predict the radiotherapeutic response of GBM patients. Methods. The MRI images, genetic data, and clinical data of 152 patients with GBM were analyzed. 122 patients from the TCIA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 40 publications
0
12
2
Order By: Relevance
“…The patients received partial ( n = 86) or gross total ( n = 90) resection followed by chemotherapy and radiation. Karnofsky Performance Status (KPS) scores (binary, score >70 or ≤70) [ 5 , 33 ], as a strong independent predictor of clinical outcome [ 34 ] determined by postoperative treatment, were retrieved from their electronic medical records. The demographic and clinical information are shown in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…The patients received partial ( n = 86) or gross total ( n = 90) resection followed by chemotherapy and radiation. Karnofsky Performance Status (KPS) scores (binary, score >70 or ≤70) [ 5 , 33 ], as a strong independent predictor of clinical outcome [ 34 ] determined by postoperative treatment, were retrieved from their electronic medical records. The demographic and clinical information are shown in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…55 The high-dimensional quantitative imaging features extracted by radiomics not only reflects the macroscopic characteristics of tumor tissues, but also the molecular characteristics, and has great prospects in HGG treatment monitoring. 56 Some studies only analysis of heterogeneity in T2WI, combined with the ML algorithm, to distinguish between GBM progress and PsP; the accuracy of the training set reached 0.88, and the AUC was 0.9, the sensitivity, specificity, accuracy of the testing set were 100.0%, 67.0%, and 86.0%, respectively. 57 When T1C and T2/Flair were combined to quantify three-dimensional shape features, and the SVM classifier was used to distinguish between progress and PsP, the accuracy of the training and test sets were 91.5% and 90.2%, respectively.…”
Section: Mri-based Machine Learning To Evaluate Treatment Responsementioning
confidence: 99%
“…The evaluation/prediction model constructed by combining MRI and ML may be an effective tool to assist clinical decision‐making in follow‐up treatment of HGG patients 55 . The high‐dimensional quantitative imaging features extracted by radiomics not only reflects the macroscopic characteristics of tumor tissues, but also the molecular characteristics, and has great prospects in HGG treatment monitoring 56 . Some studies only analysis of heterogeneity in T2WI, combined with the ML algorithm, to distinguish between GBM progress and PsP; the accuracy of the training set reached 0.88, and the AUC was 0.9, the sensitivity, specificity, accuracy of the testing set were 100.0%, 67.0%, and 86.0%, respectively 57 .…”
Section: Hgg Treatment Response Assessmentmentioning
confidence: 99%
“…Moreover, some studies have reported the accuracy of AI in predicting glioma prognosis. The cancer imaging archive (TCIA) and local test cohorts were used by Pan et al to predict the OS using ML techniques with C-indexes of 0.70 and 0.76, respectively, for multiparameter MRI of 152 GBMs (53). When radiomic characteristics were paired with preoperative clinical risk factors (C-index = 0.76 in the TCIA and test cohort), the impact of OS prediction was substantially enhanced.…”
Section: Response Assessment and Prognosis Predictionmentioning
confidence: 99%